2015
DOI: 10.1007/s11926-015-0504-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Antiphospholipid Syndrome

Abstract: Antiphospholipid syndrome (APS) is a multisystem autoimmune condition characterized by vascular thromboses associated with persistently positive antiphospholipid antibodies. There is currently a paucity of data (incidence, prevalence, thrombosis risk, and effective treatment) in pediatric APS. The purpose of this report is to review the current literature on APS in children and neonates, identify the gaps in current knowledge, and suggest avenues for studies to fill those gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 122 publications
1
29
0
2
Order By: Relevance
“…Furthermore, more recently, only few studies reported evidence of the beneficial use of IVIG to treat pediatric aPL-related chorea [9,10,[12][13][14][15]. Our clinical case confirmed the importance of the early use of IVIG treatment in CIDP children with aPL positivity.…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, more recently, only few studies reported evidence of the beneficial use of IVIG to treat pediatric aPL-related chorea [9,10,[12][13][14][15]. Our clinical case confirmed the importance of the early use of IVIG treatment in CIDP children with aPL positivity.…”
Section: Resultssupporting
confidence: 80%
“…The role of immunotherapy has not been established and is usually reserved for patients with concurrent autoimmune diseases such as SLE. 135…”
Section: Antiphospholipid Antibody Syndromementioning
confidence: 99%
“…Alternatively, APS can be secondary to an autoimmune disorder-most commonly SLE-which is the attributed cause of $80% of pediatric cases of secondary APS. 4,41 Children with APS typically demonstrate arterial and deep vein thromboses and pulmonary emboli. 4 Thrombocytopenia, hemolytic anemia, and Evans syndrome (an autoimmune condition characterized by destruction of red blood cells, white blood cells, and platelets) represent hematologic manifestations; skin (Raynaud's phenomenon and livedo reticularis), kidney, heart, and neurologic involvement can also occur.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…4 Thrombocytopenia, hemolytic anemia, and Evans syndrome (an autoimmune condition characterized by destruction of red blood cells, white blood cells, and platelets) represent hematologic manifestations; skin (Raynaud's phenomenon and livedo reticularis), kidney, heart, and neurologic involvement can also occur. 41…”
Section: Treatment and Prognosismentioning
confidence: 99%